IMPLEMENTASI METODE KHIDMAH TERHADAP PEMBENTUKAN KEPRIBADIAN PESERTA DIDIK DI SMKS NURUL HAROMAIN PUJON KAB. MALANG - Ahmad Syaifudin Zuhri; Ibnu Jazari; Moh Muslim (VICRATINA, 2020)
The personality of the current generation really needs special attention by the school institutions and the school teachers, by the era of globalization which is very free and very broad making demands as a companion for them, there is a new breakthrough in the way of teaching and learning to be something that very needed. By choosing the khidmah method in Nurul Haromain SMKS, the researchers interested to examine how the concept and implementation of the khidmah and the impact of this method. Because it is very rare in formal institutions that use these methods. With something unique it makes the researchers want to explore what is the breakthrough and indeed there is a very good formulation in this khidmah which is applied at Nurul Haromain SMKS.